2003
DOI: 10.1029/2002jb002201
|View full text |Cite
|
Sign up to set email alerts
|

Effective elastic thickness Te of the lithosphere in western Canada

Abstract: [1] A stochastic relationship between topography and Bouguer gravity is used to calculate high-resolution variations in effective elastic thickness, T e , of the lithosphere in western Canada. The topography-gravity coherence is calculated using a two-dimensional, maximum-entropy-based spectral estimator. This method allows for smaller data windows and provides T e determinations with higher spatial resolution than standard Fourier spectral estimators. Our analysis shows significant variations in T e in wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 40 publications
9
54
0
Order By: Relevance
“…The model has a 120 km elastic lithosphere and a 2770 km mantle, whose density and elastic properties vary vertically according to PREM (Dziewonski and Anderson, 1981). The lithospheric thickness we adopted is consistent with the estimates given by Flück et al (2003) for the Canadian Shield. The mantle is rheologically uniform, both vertically and laterally, and the deformation is controlled by a mixed flow-law (Gasperini et al, 1992), including the linear Maxwell body relation and the power-law equation shown below:…”
Section: The Modelmentioning
confidence: 93%
“…The model has a 120 km elastic lithosphere and a 2770 km mantle, whose density and elastic properties vary vertically according to PREM (Dziewonski and Anderson, 1981). The lithospheric thickness we adopted is consistent with the estimates given by Flück et al (2003) for the Canadian Shield. The mantle is rheologically uniform, both vertically and laterally, and the deformation is controlled by a mixed flow-law (Gasperini et al, 1992), including the linear Maxwell body relation and the power-law equation shown below:…”
Section: The Modelmentioning
confidence: 93%
“…As for the Forsyth approach with a variable z m (x), the wavelet-adapted equations for the Banks method can account for a variable z l (x) if this information is known. Generally speaking, the inclusion of a thin layer between the surface and Moho serves to reduce T e estimates, though not significantly, with 1999] and Flück et al [2003] finding their results to be fairly insensitive to the magnitude of the density contrasts or depth of the interface, albeit using different approaches to that of Banks et al [2001].…”
Section: C2 Banks Methodsmentioning
confidence: 99%
“…Thinnest elastic thickness on the North American Craton, <40 km, is found beneath the Williston Basin in southern Saskatchewan correlative (2) Shaocheng, J., Rondenay, S., Mareschal, M., and Seneschal, G., 1996 1985Majorowicz and Gough (1991; Gough and Majorowicz (1992); Majorowicz et al (1993aMajorowicz et al ( , 1993b; Majorowicz and Gough (1994) (2014) with the trace of the Trans-Hudson Orogen. For the Cordillera, elastic thickness is in the range 20-40 km (Fluck et al 2003).…”
Section: Elastic Thicknessmentioning
confidence: 99%